Importance of geometallurgy in the gold deposits of the future in Peru - Castillo Mamani, Jhonny Handry (2022)
Currently, we are facing an increasing demand for minerals, including gold. The benefits of gold mining in the country are reflected in its contribution to exports and tax revenues. Geometallurgy seeks to significantly reduce the impact of spatial uncertainty in mine planning because it documents the variability in a gold deposit, this minimizes the risk of the project in future exploitation. Therefore, this study raises the need for the Peruvian mining activity to implement geometallurgy in its operations and processes; to reduce the negative effects on the environment and achieve the maximum use of natural resources. The importance of geometallurgy lies in the qualification of gold deposits, based on their physical-mechanical and textural properties, process mineralogy, and chemical-metallurgical analysis. These studies provide information for conducting metallurgical leaching tests and determining factors that could affect processing.